Rampant Development of Water Diversion Projects as a Threat to Fish Diversity: A Case of the Modi Khola (Hydro Nepal: Journal of Water, Energy and Environment, 2019)
The current focus of the country in meeting the increasing demands for energy has led to the increase in number of river water diversion projects for hydropower generation. But the lack of proper guidelines and monitoring mechanism has resulted in rampant licensing of hydropower projects. There are no rules for determining the appropriate number of water diversion projects in a single river. By discussing the case of rampant water diversion projects in the Modi Khola, of western Nepal, this paper raises an important issue of environmental feasibility of projects in the context where, only the engineering and economic feasibility of a project is taken as the basis for project approval and implementation.